Penokohan Pada Cerita Pendek karya Raditya Dika di Platform Medium - Ariyadi, Tara Merischa; Farida Yufarlina Rosita (ESTETIK : Jurnal Bahasa Indonesia, 2025)
This research aims to analyze characterization techniques in short stories by Raditya Dika published on the Medium platform. Using qualitative descriptive methods, data was collected through reading and recording dialogue and character interactions in several short stories. The research results show that Raditya Dika succeeded in creating lively and relatable characters through detailed descriptions, intelligent dialogue and distinctive humor. The characterization techniques used add depth and meaning to his short stories, reflecting sharp observations of human nature and social dynamics. This research reveals that the characters in Dika's works not only function to move the plot of the story, but also enrich the narrative and leave a deep impression on the reader.